MODIFIED VERSUS CLASSICAL HONG KONG OPERATION FOR SPINAL TUBERCULOSIS: Spinal Tuberculosis - Afzal, Dr Waseem; Qureshi, Muhammad Asad; Khalique, Ahmed Bilal; Pasha, Ibrahim Farooq; Ali, Usman Bin (Pakistan Armed Forces Medical Journal, 2012)
Objective: To compare Classical Hong Kong (CHK) and Modified Hong Kong (MHK) operations as treatment options for spinal tuberculosis.Study Design: Retrospective analytical studyPlace and Duration of Study: Combined Military Hospital (CMH), Rawalpindi, Pakistan, from Jan 2002 till Dec 2007.Patients and Methods: Out of 100 consecutive patients managed surgically by Classical or Modified Hong Kong Operations, 60 patients were selected for this study depending upon the selection criteria.Results: Twenty patients were in CHK group and forty patients were in MKH group. Both of these groups matched for age, gender and involvement of spinal levels with tuberculosis. Neurological recovery in CHK group was 31.8% while in MHK group it was 40.0 %. Correction of deformity was 25.0% in CHK while 30.3% in MHK.Conclusion: There was no statistical difference between CHK and MHK operations for spinal tuberculosis considering neurological improvement and correction of deformity in our study.